Human involvement with the rise of artificial intelligence in the realm of Geospatial Health - Mahdi Fallah; Tajoddin Karami; Moosa Kamanroodi Kojouri (Boletín Geográfico)
In the era of Web 3, digital currencies and virtual cities, human decision-making is very special. In It´s crucial to examine human responses alongside artificial intelligence in the healthcare field following an event and to create a collaborative geographic system based on modern technology. The ultimate goal is the restoration of countries´ essential services prioritizing health.